Determinan Kinerja Manajerial Dimoderasi Locus of Control - Anggun Alifia Fatmah; Dahlia Tri Anggraini (Universitas Muhammadiyah Jakarta, 2022)
This research to determine the effect of participatory budgeting, clarity of budget targets, and organizational commitment to managerial performance with locus of control as a moderating variable. By using nonprobability sampling technique and purposive sampling method, the researcher distributed questionnaires to 67 respondents including supervisors, managers, and senior managers at PT Tiki Jalur Nugraha Ekakurir (JNE) in the DKI Jakarta area. The data analysis technique uses moderated regression analysis with SPSS Version 23. This study shows that participatory budgeting, clarity of budget targets, and organizational commitment partially have a positive and significant effect on managerial performance. And locus of control can significantly strengthen the influence of participatory budgeting and organizational commitment on managerial performance. However, locus of control does not significantly strengthen the clarity of budget targets on managerial performance.